Climate-Induced Drought, Food Insecurity, and Adaptation Governance: A Multiscale Review of Risks and Policy Responses in Africa and South Asia - Himank Sharma (International Journal of Environmental Planning and Development Architecture, 2026)
Drought is one of the most critical climate-induced hazards, severely affecting agricultural systems, water resources, and human well-being, particularly in Sub-Saharan Africa and South Asia. This review provides a comprehensive analysis of the multidimensional impacts of drought by examining its effects on food security, population displacement, and institutional adaptation across selected case studies from West Africa, South Africa, and coastal Bangladesh. The findings reveal that increasing climate variability and prolonged dry conditions significantly reduce crop productivity, disrupt livestock systems, and undermine rural livelihoods, thereby exacerbating food insecurity and economic vulnerability. The paper also highlights the growing challenges faced by internally displaced populations in climate-sensitive regions, where inadequate access to healthcare, sanitation, and essential services intensifies health risks and social marginalization. In evaluating adaptation responses, the study explores the role of climate-smart agriculture, community-based adaptation, and ecosystem-based approaches in strengthening resilience. While these strategies demonstrate strong potential, their effectiveness is often constrained by limited financial resources, weak institutional coordination, insufficient extension services, and restricted access to climate information. Furthermore, the review identifies critical gaps in governance frameworks, particularly the disconnect between policy formulation and on-the-ground implementation. Marginalized communities, including smallholder farmers and displaced populations, remain underrepresented in adaptation planning processes. The study emphasizes the need for integrated, participatory, and multilevel governance systems that connect agriculture, health, and climate policies. Key recommendations include strengthening early warning systems, enhancing local knowledge integration, and improving access to adaptation finance. Overall, this review contributes valuable insights for policymakers and practitioners by outlining scalable, inclusive, and sustainable strategies to enhance drought resilience in highly vulnerable regions.
Keywords: Climate-induced hazards; Food security; climate-smart agriculture; drought; institutional adaptation